A retrospective study: Analysis of factors related to readmission of schizophrenia patients - Ni Luh Putu Inca Buntari Agustini; Ketut Citra Paramitasari; Ida Ayu Ningrat Pangruating Diyu; Made Dian Shanti Kusuma (Jurnal Keperawatan Padjadjaran, 2026)
Background: Hospital readmission among patients with schizophrenia is an important indicator of healthcare quality and the effectiveness of community-based support. Readmissions are influenced by a complex interplay of clinical and environmental factors that affect patients' long-term recovery and stability. Purpose: This study aimed to identify factors associated with hospital readmission among patients with schizophrenia at the Bali Provincial Mental Hospital. Methods: A retrospective cross-sectional study was conducted using medical records of patients diagnosed with schizophrenia who received treatment at the Bali Provincial Mental Hospital in 2023. From a total population of 2,669 eligible medical records, 401 were selected through simple random sampling. Data were analyzed using descriptive statistics, chi-square tests for bivariate analysis, and multivariable logistic regression to identify factors independently associated with readmission. Results: Four factors were significantly associated with hospital readmission among patients with schizophrenia: age (*p* = 0.038), residual symptoms (*p* = 0.003), medication adherence (*p* < 0.001), and comorbidities (*p* < 0.001). Among these, medication adherence was the strongest predictor of readmission, with an adjusted odds ratio (AOR) of 83.902. Conclusion: Age, residual symptoms, medication adherence, and comorbidities were independently associated with hospital readmission among patients with schizophrenia. Strengthening medication adherence through family supervision and comprehensive management of residual symptoms and comorbid conditions may help reduce the risk of readmission and improve long-term clinical outcomes.